2013 25th Euromicro Conference on Real-Time Systems 2013
DOI: 10.1109/ecrts.2013.13
|View full text |Cite
|
Sign up to set email alerts
|

Reducing Tardiness under Global Scheduling by Splitting Jobs

Abstract: Under current analysis, tardiness bounds applicable to global earliest-deadline-first scheduling and related policies depend on per-task worst-case execution times. By splitting job budgets to create subjobs with shorter periods and worst-case execution times, such bounds can be reduced to near zero for implicit-deadline sporadic task systems. However, doing so will result in more preemptions and could create problems for synchronization protocols. This paper analyzes this tradeoff between theory and practice … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
7
0

Year Published

2014
2014
2023
2023

Publication Types

Select...
4
1

Relationship

3
2

Authors

Journals

citations
Cited by 7 publications
(7 citation statements)
references
References 16 publications
0
7
0
Order By: Relevance
“…1, functions in this way. Erickson et al [8] also showed that response time bounds can be further improved by simulating a G-FL schedule of a task system with more frequent releases of smaller jobs. This method is referred to as job splitting.…”
Section: Determining End-to-end Latencymentioning
confidence: 99%
See 4 more Smart Citations
“…1, functions in this way. Erickson et al [8] also showed that response time bounds can be further improved by simulating a G-FL schedule of a task system with more frequent releases of smaller jobs. This method is referred to as job splitting.…”
Section: Determining End-to-end Latencymentioning
confidence: 99%
“…We randomly generated DAGs of varying characteristics and tested them for schedulability using the methods described in [8]. We now describe the experimental process we used.…”
Section: Schedulability Experimentsmentioning
confidence: 99%
See 3 more Smart Citations